Pengaruh Dress Well Terhadap Kepercayaan Diri Mahasiswa BKI - Fitriyani; Isak Iskandar (Jurnal Riset Multidisiplin Edukasi, 2025)
Self-confidence is a positive attitude that plays an essential role in supporting achievement and personal development. One of the factors believed to contribute to the level of self-confidence is the habit of dressing well. This study aims to analyze the influence of dressing well on the self-confidence of university students. A quantitative approach was employed with an associative research design to examine the relationship between two variables: dressing well (X) and self-confidence (Y). Data were collected through questionnaires and analyzed using statistical methods. The results indicate a significant influence of dressing well on students’ selfconfidence. These findings suggest that dressing neatly and appropriately not only enhances physical appearance but also supports the development of character and self-confidence in academic settings. This research is expected to serve as a basis for developing strategies to improve student self-development through appearance.